Efektivitas Pelaksanaan Program Pengembangan UKM Di Dinas Koperasi dan Usaha Mikro, Kecil dan Menengah Kota Manado - Karauwan, Naritza Mirlithia; Laloma, alden; Tampongangoy, Deysi Livi (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: Small and medium enterprises is one of the important part of the economy of acountry or region, as well as the State of Indonesia. Small and medium businesses have animportant role in its economy of the community. However, in the development of small andmedium enterprises still seems to be hampered by a few things such as lack of capital and also thesoul of entrepreneurship. Given the small and Medium Businesses recognised as employment formost workers, then the necessary development of partially, because as long as this does not givemaximum results against small and Medium Business performance improvements.In this study, the researchers used a qualitative research design with a contextualresearch which makes human beings as instruments, and adapted to the situation are reasonablein relation to the collection of data.Seen from the ability of human resources Department alreadyowned are effective because they already provided insight on coaching and training for small andMedium Businesses in accordance with the law, but still required construction in terms of thesense of responsibility in order to carry out the task and his work well in improving the well-beingof small and medium businessmen rather than for personal gain, bureaucracy, or a certain type tobe reaching the goal is efficient.Keywords: Effectiveness, development UKMPENDAHULUANUsaha Kecil Menengah (UKM)merupakan salah